67 Breast biopsy patterns and findings among older women undergoing screening mammography: what is the impact of age and comorbidity?. (4th December 2019) - Braithwaite, Dejana; Advani, Shailesh; Abraham, Linn; Buist, Diana; O'Meara, Ellen; Miglioretti, Diana; Sprague, Brian; Henderson, Louise; Onega, Tracy; Schousboe, John; Zhang, Dongyu; Demb, Joshua; et al.
Abstract : Purpose: Biopsy use and findings following screening mammography among older women are not well established. Method: We included 171, 636 women ages 66–99 years with at least one screening mammogram from the Medicare-linked Breast Cancer Surveillance Consortium (BCSC, 1999–2010). We calculated percentage of screens followed by biopsy within 90 days by age and comorbidity. Results: Among 527, 254 screening mammograms, 6587(1.2%) were followed by biopsy within 90 days. Whereas proportions of screens followed by any biopsy did not vary significantly by age groups (ages 66–74:1.3%, ages 75–84: 1.2%, ages 85–99:1.2%, p trend =0.07), they increased with increasing Charlson Comorbidity score (CCS) ([ages 66–74: CCS0:1.2%, CCS1: 1.3%, CCS≥2:1.6%; p trend =<0.001]; [ages 75–84:CCS0: 1.2%, CCS1:1.3%, CCS≥2:1.3%; p trend =0.01]; [ages 85–99: CCS0:1.1%, CCS1:1.2%, CCS≥2:1.4%; p trend =0.16]). Further, proportions of benign biopsy increased with increasing CCS across all age groups (ages 66–74: CCS0:0.77%, CCS1:0.88%, CCS≥2:0.94%, p trend <0.001; ages 75–84: CCS0:0.62%, CCS1:0.75%, CCS≥2:0.78%, p trend =0.001 and ages 85–99: CCS0:0.48%, CCS1:0.57% and CCS≥2:0.61%, p trend =0.23). Proportions of any biopsy with a result of invasive cancer did not vary significantly by CCS across all age groups ([ages 66–74: CCS0:28.4%, CCS1:25.5%, CCS≥2:30.8%; p trend =0.93]; [ages 75–84: CCS0:37.2%, CCS1:36.0%, CCS≥2:32.0%; p trend =0.15]; [ages 85–99: CCS0:46.8%, CCS1:43.5%, CCS≥2:43.8%; p trend =0.60]). Conclusions: Whereas proportions of screening mammograms followed by biopsy did not differ significantly by age group, proportions increased with increasing comorbidity, overall and within age groups, resulting in lower invasive cancer yield for the oldest age groups. Proportions of benign biopsy also increased with increasing comorbidity. These results highlight that older women with significant comorbidity may be harmed by downstream procedures following screening mammography. Acknowledgements: This study was supported by the U.S. National Cancer Institute 1R01CA207361-01A1 grant (to Dr. D. Braithwaite) and BCSC P01CA154292 grant. We thank all study participants and BCSC staff.